The Impact of Cropping Systems on Soil Health: A Focus on the Teesta-Terai Alluvial Zone of West Bengal, India - Amiya Biswas; Dibyendu Mukhopadhyay; Rohit Kumar Choudhury; Asim Biswas (Journal of the Indian Society of Soil Science, 2025)
This comprehensive review examines the intricate relationships between various cropping systems and soil health, with a particular emphasis on the Teesta-Terai Alluvial zone of West Bengal, India. Soil health, defined as the continued capacity of soil to function as a vital living ecosystem, is critical for sustainable agriculture, especially in India where agriculture contributes 18.33% to GDP. Despite extensive research, significant gaps exist in long-term studies (>20 years), comprehensive understanding of soil biological indicators, climate-crop-soil interactions, and region-specific soil health assessments in the Teesta-Terai zone. A systematic literature review was conducted using multiple databases (Web of Science, Scopus, Google Scholar, AGRIS) covering peer-reviewed articles from 2000-2023, focusing on rice-based, wheatbased, jute-based, and maize-based cropping systems. Rice-based systems showed complex impacts with improved nutrient availability under flooded conditions but reduced soil porosity and increased methane emissions. Wheat-based rotations demonstrated positive effects on soil structure and nutrient cycling. Jutebased systems significantly improved soil physical properties and organic matter content. Maize-based systems contributed to enhanced soil biological activity and carbon sequestration. The study reveals that crop diversification and integrated soil health management are essential for maintaining soil health while meeting productivity demands. The research identifies critical needs for long-term studies, development of region-specific soil health indicators, and integration of modern monitoring technologies for sustainable soil management in the Teesta-Terai Alluvial zone.